Homoarginine in patients with primary hyperparathyroidism - Tomaschitz, Andreas; März, Winfried; Ritz, Eberhard (The American journal of the medical sciences, 2015)
Low levels of the amino acid homoarginine and parathyroid hormone (PTH) excess are both independently related to an increased risk of cardiovascular morbidity and mortality. Accumulating evidence points to a mutual interplay between homoarginine and PTH. The authors therefore aimed to investigate circulating homoarginine levels in patients with and without primary hyperparathyroidism (PHPT). The authors performed a cross-sectional analysis of serum homoarginine levels in 59 patients with mild and severe PHPT and in 92 control persons matched for age, sex and estimated glomerular filtration rate. Median PTH and serum homoarginine concentrations were 99.1 (79.7-120.2) pg/mL and 1.16 (0.95-1.66) mmol/L in patients with PHPT (79.7% female; 42.4% with normocalcemia) as compared with 45.8 (36.4-53.9) pg/mL and 1.62 (1.33-2.04) mmol/L in the control group (P < 0.001 for both), respectively. The authors observed no statistically differences between cases and controls for 25-hydroxyvitamin D [25(OH)D], serum albumin, hemoglobin, waist-to-hip ratio, C-reactive protein and NT-pBNP values. Multivariate analysis of covariance revealed that patients with PHPT had significantly lower homoarginine levels than controls (P < 0.001). This difference remained significant after adjusting for multiple confounders such as 25(OH)D, body mass index, LDL cholesterol, albumin, calcium, hemoglobin, smoking status and current antihypertensive medication. The differences of homoarginine levels persisted even after exclusion of patients with estimated glomerular filtration rate <60 mL/min (P = 0.003) and 25(OH)D levels <30 ng/mL (P = 0.001), respectively. Patients with PHPT have lower homoarginine levels compared with matched controls irrespective of age, sex, kidney function and 25(OH)D status. Further studies are needed to evaluate whether low homoarginine accounts for higher cardiovascular risk conferred by PTH excess.
Gesehen am 25.07.2017